The Business Ethics of Jamsetji Nusserwanji Tata – A Forerunner in Promoting Stakeholder Welfare - Sivakumar, N. (Journal of business ethics, 2008)
This article examines the business practices of Jamsetji Nusserwanji Tata, the founder the Tata group of business in India in the 19th century, from the perspective of stakeholder welfare. Jamsetji Nusserwanji Tata was concerned about the welfare of all major stakeholder constituents. His business practices promoted the welfare of employees, customers, society, owners, competitors, environment and other stakeholders. He implemented several measures even before law mandated them thus acting as a forerunner in promoting stakeholder welfare. His business plans became the foundation for an economically strong India. This article, after an initial overview of the stakeholder framework, describes the business practices of Jamsetji Nusserwanji Tata with regard to major stakeholder constituents. Relevant research findings regarding each stakeholder constituent studied have been cited to show that the practices of Jamsetji Nusserwanji Tata have relevance to business even today.